SMA Syndrome – Wait & Nurture - Saw, Shier Khee; Zulkifli, Ahmad Zuraimi; Nadarajan, Chandran; Soh, Jien Yen; Mohammad Azmi, Mohd Azem Fathi; Syed Abd Aziz, Syed Hassan; Wong, Michael Pak-Kai (Malaysian Journal of Medicine and Health Sciences, 2022)
Superior mesenteric artery (SMA) syndrome is rare with the common presentation of megaduodenum from entrapment of the third part of the duodenum (D3) by the SMA. We present a case report of a thin, fit 16-year-old boy, active smoker complaining of generalized colicky abdominal pain associated with persistent postprandial vomiting. Small bowel study demonstrated partial duodenal obstruction from compression of the third part of the duodenum by the SMA. Computed tomography of the abdomen shows an aorto-mesenteric angle of 13 degrees with aorto-mesenteric distance of 0.32 cm, indicating SMA syndrome. His symptoms resolved spontaneously with watchful waiting and nutritional care plan. The success was contributed to restoring the fat cushion around the SMA, hence, widening the aorto-mesenteric angle. In conclusion, watchful waiting with a nutritional care plan is a feasible initial strategy in the approach to SMA syndrome. However, should this strategy be unsuccessful, the choice of surgical treatment is duodenojejunostomy.